Violence in Education: A Bibliometric Analysis from Scopus Database - Budianti, Yusnaili; Ruwaidah, Ruwaidah; Megawati, Betti (Universitas Pahlawan Tuanku Tambusai, 2023)
This study presents a bibliometric analysis of research on violent education. Using the Scopus database, the study examines research articles containing the term